The Resistance of Soluble Derivatives of Fibrinogen and the Sensitivity of Its Insoluble Forms to Fibrinolytic Degradation in Blood - Gurewich, Victor; Nowak, Andrzej; Lipinska, Izabella; Lipinski, Boguslaw (Thrombosis and Haemostasis, 1974)
The effect of naturally induced fibrinolytic activity on fibrinogen and certain soluble and insoluble derivatives was studied. Experiments were performed on blood removed after venous occlusion of the arm and immediately after death. A previously described electrophoretic method was used by which the heterogeneity of fibrinogen can be demonstrated directly in intact plasma. It was shown that fibrinogen, soluble fibrin monomer (FM) complexes and fibrin degradation products are resistant to degradation by naturally-induced fibrinolytic activity. By contrast, rapid lysis of fibrin, protamine sulfate (PS) precipitated fibrinogen, and PS and ethanol induced gels of FM occurred. The observations are believed relevant to our understanding of the pathway of fibrinogen and FM catabolism and the interpretation of the origin of serum FDP.